Ceftolozane/tazobactam and ceftazidime/avibactam for the treatment of complicated intra-abdominal infections - Goodlet KJ; Nicolau DP; Nailor MD (Dove Medical Press, 2016)
Kellie J Goodlet,1 David P Nicolau,2 Michael D Nailor1,3 1Department of Pharmacy Services, Hartford Hospital, Hartford, CT, USA; 2Center of Anti-Infective Research, Hartford Hospital, Hartford, CT, USA; 3Department of Pharmacy Practice, School of Pharmacy, University of Connecticut, Storrs, CT, USA Abstract: Complicated intra-abdominal infections (cIAI) represent a large proportion of all hospital admissions and are a major cause of morbidity and mortality in the intensive care unit. Rising rates of multidrug resistant organisms (MDRO), including extended-spectrum β-lactamase producing Enterobacteriaceae and carbapenem-nonsusceptible Pseudomonas spp., for which there are few remaining active antimicrobial agents, pose an increased challenge to clinicians. Patients with frequent exposures to the health care system or multiple recurrent IAIs are at increased risk for MDRO; however, treatment options have traditionally been limited, in some cases necessitating the utilization of last-line agents with unfavorable side-effect profiles. Ceftolozane/tazobactam and ceftazidime/avibactam are two new cephalosporin and β-lactamase inhibitor combinations with recent US Food and Drug Administration approvals for the treatment of cIAI in combination with metronidazole. Ceftolozane/tazobactam has demonstrated excellent in vitro activity against MDR and extensively drug-resistant Pseudomonas spp., including carbapenem-nonsusceptible strains, while ceftazidime/avibactam effectively inhibits a broad range of β-lactamases, making it an excellent option for the treatment of carbapenem-resistant Enterobacteriaceae. Both agents were shown to be noninferior to meropenem for treatment of cIAI in Phase III trials; however, reduced responses in patients with renal impairment at baseline highlight the importance of routine serum creatinine monitoring and ongoing dose adjustments. This review highlights in vitro and in vivo data of these two agents and suggests their proper place in cIAI treatment to ensure adequate therapy in our most at-risk patients while sparing unnecessary use in patients without MDRO risk factors. Keywords: resistance, antimicrobials, carbapenamase, Pseudomonas aeruginosa, KPC